The perceived effectiveness of online social work education: insights from a national survey of social work educators. Issue 6 (18th August 2018) - Levin, Shelley; Fulginiti, Anthony; Moore, Brenda
ABSTRACT: Despite rapid growth in online learning in social work and a growing body of research showing comparable levels of effectiveness and student satisfaction, concerns about online social work education remain among faculty. This is important given that faculty acceptance can play a pivotal role in the success and failure of online education. The current study aimed to compare levels of perceived effectiveness of online and on-the-ground education across nine social work competencies, as well as examine the association between experience with online education and perceived effectiveness of online education. The sample included 376 faculty recruited from schools of social work in the United States. Results suggest that online education is consistently perceived as being less effective than on-the ground education in helping students to meet Council on Social Work Education competencies. Furthermore, perceptions of effectiveness of online education are lowest for practice-oriented competencies. Regression analyses showed that tenure status, years of full-time teaching, technological preparedness, and level of exposure to online education were significantly associated with perceived effectiveness of online education. It is critical that schools develop more opportunities for faculty to engage in direct teaching experience online as well as enhance their levels of comfort and proficiency with technology.